The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/vaccines11020229
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox (MPOX)-Related Knowledge and Vaccination Hesitancy in Non-Endemic Countries: Concise Literature Review

Abstract: In May 2022, the world witnessed the emergence of human monkeypox (MPOX), a new zoonotic viral disease in multiple non-endemic countries. This health threat has been associated with increased anxiety, especially after the COVID-19 catastrophe. In addition, people are exposed to an unprecedented amount of information, making them vulnerable to misinformation that may lead to embracing conspiracy theories. This literature review was conducted to evaluate the levels of MPOX-related knowledge and attitudes toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 31 publications
1
29
1
Order By: Relevance
“…In contrast to the previous studies that warned of the low level of knowledge regarding Mpox and its subsequent negative effect on outbreak response in terms of awareness of risks and preventive measures, our results did not show a statistically significant impact of Mpox knowledge on the intention to receive the vaccine [ 57 , 89 ]. Previous studies showed that unsatisfactory Mpox knowledge is commonplace among health professionals [ 41 , 43 , 89 , 108 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the previous studies that warned of the low level of knowledge regarding Mpox and its subsequent negative effect on outbreak response in terms of awareness of risks and preventive measures, our results did not show a statistically significant impact of Mpox knowledge on the intention to receive the vaccine [ 57 , 89 ]. Previous studies showed that unsatisfactory Mpox knowledge is commonplace among health professionals [ 41 , 43 , 89 , 108 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the finding of an Mpox vaccine acceptance rate of only 29% is lower compared to the pooled estimate in a recent meta-analysis that involved HCWs surveyed in four different studies showing an acceptance rate of 63% [ 43 , 56 , 79 , 80 , 81 ]. Additionally, a recent review by Lounis and Riad pointed to the issue of possible Mpox vaccination hesitancy among health professionals despite the higher rates of vaccine acceptance compared to the rates reported among the general public worldwide [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dukers-Muijrers and colleagues found that 81.5% of the MSM surveyed in the Netherlands were willing to receive an Mpox vaccine [ 42 ]. However, the willingness rate of Mpox vaccination varied among different populations and regions [ 43 ]. In the general population, the willingness rate to get the Mpox vaccine ranged from 29% in Romania to 50.6% in Saudi Arabia [ 25 , 44 ].…”
Section: Discussionmentioning
confidence: 99%